Examining the Efficiency of the Foreign Exchange Market in Iran with a Random Walk Approach - Bita Shayegani; Mahdi Fadaei; Abolfazl Shahabadi; Abbas Hamzehkhani (پژوهش‌های برنامه و توسعه)
The efficiency of the foreign exchange market is crucial because exchange rates play a vital role in balancing a nation's internal and external economies. Iran's foreign exchange market has undergone significant developments and fluctuations in recent years, impacting its efficiency. This is evident in the monthly time series data for the unofficial exchange rates of the dollar, euro, and yuan from 2001 to 2021. An interesting trend has emerged since 2017: the Chinese yuan appears to be gradually replacing the dollar and euro as the primary trading currency in Iran's international market. Statistical tests, including the Augmented Dickey-Fuller (ADF), Phillips-Peron (PP), and KPSS tests, indicate weak-form efficiency in the markets for all three currencies (dollar, euro, and yuan). This suggests that these markets remain vulnerable to speculative attacks. Furthermore, Johansen's cointegration and Granger's causality tests reveal an absence of semi-strong efficiency in all three markets. This implies that past price information alone is insufficient to predict future exchange rates. The research findings suggest that choosing the yuan as an alternative currency has had a somewhat positive impact on improving the efficiency of the Iranian currency market.